2014
DOI: 10.1016/j.celrep.2014.08.066
|View full text |Cite
|
Sign up to set email alerts
|

HOIP Deficiency Causes Embryonic Lethality by Aberrant TNFR1-Mediated Endothelial Cell Death

Abstract: Linear ubiquitination is crucial for innate and adaptive immunity. The linear ubiquitin chain assembly complex (LUBAC), consisting of HOIL-1, HOIP, and SHARPIN, is the only known ubiquitin ligase that generates linear ubiquitin linkages. HOIP is the catalytically active LUBAC component. Here, we show that both constitutive and Tie2-Cre-driven HOIP deletion lead to aberrant endothelial cell death, resulting in defective vascularization and embryonic lethality at midgestation. Ablation of tumor necrosis factor r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
314
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(337 citation statements)
references
References 52 publications
20
314
3
Order By: Relevance
“…Like FIP200-4A homozygous knock-in mice, ablation of TNFR1 in FIP200 knockout mice prevented the lethality by E16.5 observed previously (Gan et al 2006). These results are consistent with recent reports suggesting a critical role of the TNFα pathway as a "checkpoint" during embryogenesis that triggers embryonic lethality in response to various defects of knockout animals (Dillon et al 2014;Peltzer et al 2014). On the other hand, whereas FIP200-4A homozygous knock-in mice survived until birth, TNFR1 knockout did not allow completion of embryogenesis of FIP200 knockout mice.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Like FIP200-4A homozygous knock-in mice, ablation of TNFR1 in FIP200 knockout mice prevented the lethality by E16.5 observed previously (Gan et al 2006). These results are consistent with recent reports suggesting a critical role of the TNFα pathway as a "checkpoint" during embryogenesis that triggers embryonic lethality in response to various defects of knockout animals (Dillon et al 2014;Peltzer et al 2014). On the other hand, whereas FIP200-4A homozygous knock-in mice survived until birth, TNFR1 knockout did not allow completion of embryogenesis of FIP200 knockout mice.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies suggested that the TNFα pathway plays a crucial role during embryogenesis and is involved in embryonic lethality caused by a variety of abnormalities in different knockout mice (Dillon et al 2014;Peltzer et al 2014). To investigate directly whether increased sensitivity to TNFα-induced cell death is responsible for the embryonic lethality of FIP200 knockout mice, we generated FIP200…”
Section: Fip200mentioning
confidence: 99%
“…The importance of the linear ubiquitin pathway in the regulation of innate immune responses has been demonstrated in murine models. Mice deficient in LUBAC subunits have variable degrees of inflammation, from a mild phenotype in HOIL-1-deficient mice (16) to more severe inflammation and dermatitis in SHARPIN KO (2,17) to defective vascularization and embryonic lethality in HOIP KO (18). Consistent with the essential function of OTULIN in regulation of multiple signaling pathways, OTULINdeficient mice (gumby/gumby) are embryonic lethal due to vascular and neuronal defects caused by dysregulation in canonical Wnt signaling (8).…”
Section: Discussionmentioning
confidence: 77%
“…In addition, recent studies have indicated that the lack of linear ubiquitination in complex I accelerates complex II formation in TNF signaling. 77 Whereas CYLD directly binds LUBAC and removes linear chains, thereby sensitizing cells to TNF-provoked apoptosis, A20 binding to the linear chains via its ZnF7 domain antagonizes their removal, consequently blocking cell death. 78 Dissimilarly, the RIP1-independent apoptotic branch is controlled by the level of cellular FLICE Inhibitory Protein (c-FLIPL), which effectively blocks caspase-8 activation by competitively binding to FADD.…”
Section: Apoptosis Regulation By the Ubiquitin Systemmentioning
confidence: 99%